Comparative attainment of 5-year undergraduate and 4-year graduate entry medical students moving into foundation training - Manning, Gillian; Garrud, Paul (BioMed Central, 2009)
Background Graduate entry medicine is a recent innovation in UK medical training. Evidence is sparse at present as to progress and attainment on these programmes. Shared clinical rotations, between an established 5-year and a new graduate entry course, provide the opportunity to compare achievement on clinical assessments. To compare completion and attainment on clinical phase assessments between students on a 4-year graduate entry course and an established 5-year undergraduate medicine course.